Assessment of DOAC in GEriatrics (Adage Study): Rivaroxaban/Apixaban Concentrations and Thrombin Generation Profiles in NVAF Very Elderly Patients - Foulon-Pinto, Geoffrey; Lafuente-Lafuente, Carmelo; Jourdi, Georges; Guen, Julien Le; Tall, Fatoumata; Puymirat, Etienne; Delrue, Maxime; Rivière, Léa; Ketz, Flora; Gouin-Thibault, Isabelle; Mullier, François; Gaussem, Pascale; Pautas, Eric; Lecompte, Thomas; Curis, Emmanuel; Siguret, Virginie (Thrombosis and Haemostasis, 2023)
Background Although a growing number of very elderly patients with atrial fibrillation (AF), multiple conditions, and polypharmacy receive direct oral anticoagulants (DOACs), few studies specifically investigated both apixaban/rivaroxaban pharmacokinetics and pharmacodynamics in such patients.Aims To investigate: (1) DOAC concentration–time profiles; (2) thrombin generation (TG); and (3) clinical outcomes 6 months after inclusion in very elderly AF in-patients receiving rivaroxaban or apixaban.Methods Adage-NCT02464488 was an academic prospective exploratory multicenter study, enrolling AF in-patients aged ≥80 years, receiving DOAC for at least 4 days. Each patient had one to five blood samples at different time points over 20 days. DOAC concentrations were determined using chromogenic assays. TG was investigated using ST-Genesia (STG-ThromboScreen, STG-DrugScreen).Results We included 215 patients (women 71.1%, mean age: 87 ± 4 years), 104 rivaroxaban and 111 apixaban, and 79.5% receiving reduced-dose regimen. We observed important inter-individual variabilities (coefficient of variation) whatever the regimen, at Cmax [49–46%] and Cmin [75–61%] in 15 mg rivaroxaban and 2.5 mg apixaban patients, respectively. The dose regimen was associated with Cmax and Cmin plasma concentrations in apixaban (p = 0.0058 and p = 0.0222, respectively), but not in rivaroxaban samples (multivariate analysis). Moreover, substantial variability of thrombin peak height (STG-ThromboScreen) was noticed at a given plasma concentration for both xabans, suggesting an impact of the underlying coagulation status on TG in elderly in-patients. After 6-month follow-up, major bleeding/thromboembolic event/death rates were 6.7%/1.0%/17.3% in rivaroxaban and 5.4%/3.6%/18.9% in apixaban patients, respectively.Conclusion Our study provides original data in very elderly patients receiving DOAC in a real-life setting, showing great inter-individual variability in plasma concentrations and TG parameters. Further research is needed to understand the potential clinical impact of these findings.
Keywords: apixaban; atrial fibrillation; elderly; rivaroxaban; thrombin generation